p38 MAPK Facilitates Crosstalk Between Endoplasmic Reticulum Stress and IL-6 Release in the Intervertebral Disc - Krupkova, Olga; Sadowska, Aleksandra; Kameda, Takuya; Hitzl, Wolfgang; Hausmann, Oliver Nic; Klasen, Juergen; Wuertz-Kozak, Karin (Frontiers in Immunology, 2018)
Degenerative disc disease is associated with increased expression of pro-inflammatory cytokines in the intervertebral disc (IVD). However, it is not completely clear how inflammation arises in the IVD and which cellular compartments are involved in this process. Recently, the endoplasmic reticulum (ER) has emerged as a possible modulator of inflammation in age-related disorders. In addition, ER stress has been associated with the microenvironment of degenerated IVDs. Therefore, the aim of this study was to analyze the effects of ER stress on inflammatory responses in degenerated human IVDs and associated molecular mechanisms. Gene expression of ER stress marker GRP78 and pro-inflammatory cytokines IL-6, IL-8, IL-1β and TNF-α was analyzed in human surgical IVD samples (n = 45, Pfirmann Grade 2-5). The expression of GRP78 positively correlated with degeneration grade in lumbar spine and IL-6, but not IL-1β and TNF-α. Another set of human surgical IVD samples (n = 25) was used to prepare primary cell cultures. ER stress inducer Thapsigargin (Tg, 100 and 500 nM) activated gene and protein expression of IL-6 and induced phosphorylation of p38 MAPK. Both inhibition of p38 MAPK by SB203580 (10 μM) and knockdown of ER stress effector CHOP reduced gene and protein expression of IL-6 in Tg-treated cells. Furthermore, the effects of an inflammatory microenvironment on ER stress were also tested. TNF-α (5 and 10 ng/ml) did not activate ER stress, while IL-1β (5 and 10 ng/ml) activated gene and protein expression of GRP78, but did not influence [Ca2+]i flux and expression of CHOP, indicating that pro-inflammatory cytokines alone may not induce ER stress in vivo. This study showed that IL-6 release in the IVD can be initiated following ER stress and that ER stress mediates IL-6 release through p38 MAPK and CHOP. Therapeutic targeting of ER stress response may reduce consequents of harsh microenvironment in inflamed degenerated IVD.